Biodiversity of Environmental Leptospira: Improving Identification and Revisiting the Diagnosis - Thibeaux, Roman; Girault, Dominique; Bierque, Emilie; Soupé-Gilbert, Marie-Estelle; Rettinger, Anna; Douyère, Anthony; Meyer, Michael; Iraola, Gregorio; Picardeau, Mathieu; Goarant, Cyrille (Frontiers in Microbiology, 2018)
Leptospirosis is an important environmental disease and a major threat to human health causing at least 1 million clinical infections annually. There has recently been a growing interest in understanding the environmental lifestyle of Leptospira. However, Leptospira isolation from complex environmental samples is difficult and time-consuming and few tools are available to identify Leptospira isolates at the species level. Here, we propose a polyphasic isolation and identification scheme, which might prove useful to recover and identify environmental isolates and select those to be submitted to whole-genome sequencing. Using this approach, we recently described 12 novel Leptospira species for which we propose names. We also show that MALDI-ToF MS allows rapid and reliable identification and provide an extensive database of Leptospira MALDI-ToF mass spectra, which will be valuable to researchers in the leptospirosis community for species identification. Lastly, we also re-evaluate some of the current techniques for the molecular diagnosis of leptospirosis taking into account the extensive and recently revealed biodiversity of Leptospira in the environment. In conclusion, we describe our method for isolating Leptospira from the environment, confirm the usefulness of mass spectrometry for species identification and propose names for 12 novel species. This also offers the opportunity to refine current molecular diagnostic tools.